HUKUM DAN MORAL - Antoni Antoni (An Nisa'a, 2012)
In the concept of Rule of Law, idealized that should be "commander" is legal and not political or economic or other matters. With the hope that: when the law serve as commander in chief, what the objectives can be achieved with good state. However, the problem is only with the existence of a good law is sufficient to state that what the objectives of the State can be achieved and the possibility of the occurrence of irregularities or violations by State functionaries can be avoided. Therefore, in order to state what the objectives can be achieved with good, there must be integration between the moral law and its implementation.